Can second language metaphorical competence be taught through instructional intervention? A meta-analysis - Zhou, Xiaoyong; Younas, Muhammad; Omar, Abdulfattah; Guan, Lu (Frontiers in Psychology, 2022)
Background: For a long time, the traditional view regarded metaphor as a rhetorical device that served to enrich linguistic expression. With the continuous development of cognitive linguistics, foreign language educators began to realize the vital role of metaphor in foreign language education. Objectives: This study looked at how well pedagogical interventions improve metaphorical competence by looking at how well teachers teach metaphors. Method: After a rigorous literature search and selection process from the Chinese and English databases, 13 Chinese and 7 international studies with 51 effect sizes were included in this meta-analysis. With the help of the Meta-analysis 3.0 software, the literature and heterogeneity tests were done to make sure that the results of the meta-analysis were as accurate and valid as possible. Results: The effect size tests revealed that the metaphorical instructional intervention was significantly effective in general and that the instructional intervention produced a large effect size (d = 0.888) on improving learners' metaphorical abilities. Meta-regression analyses were also done to look at how the effects of the interventions might be changed by other factors. Findings: Research has shown that instructional interventions that combine prolonged input of metaphorical concepts with reinforcement of metaphorical practice can help second language learners develop metaphoric competence. Teaching puts more pressure on teachers and the learning environment, and the results of this study could help metaphorical teachers in the future.